Customary Law Contract Agreement Conflict In Inherited Land Purchase Transaction - Ach. Dlofirul Anam (Journal of Adat Recht, 2025)
Conflicts in contractual agreements over the sale of inherited land often arise from differing paradigms between customary law, which emphasizes family consensus, and positive law, which prioritizes formal legality. This study aims to analyze the differences between customary and positive law, examine conflict patterns through empirical cases, and assess the implications and urgency of harmonization between the two. Using a normative juridical method with statutory, conceptual, and case approaches, the research is supported by literature review and court decisions. The findings reveal that most conflicts stem from unilateral sales conducted by one heir without the consent of others. From the perspective of customary law, such actions violate the principle of collective ownership, while in positive law the transaction is deemed legally flawed for failing to meet the validity requirements under Article 1320 of the Civil Code. The implications include the annulment of sale and purchase deeds, losses for bona fide buyers, and the breakdown of family solidarity. Therefore, harmonization between customary and positive law is urgently needed, particularly through state recognition of customary decisions, mandatory verification of heirs’ consent by notaries/land deed officials, and stronger synergy with the National Land Agency. This study is expected to contribute to the development of agrarian law that is both fair and responsive to Indonesia’s legal pluralism.